Biomedical applications of soy protein: A brief overview. Issue 2 (10th October 2015) - Tansaz, Samira; Boccaccini, Aldo R.
Abstract: Soy protein (SP) based materials are gaining increasing interest for biomedical applications because of their tailorable biodegradability, abundance, being relatively inexpensive, exhibiting low immunogenicity, and for being structurally similar to components of the extracellular matrix (ECM) of tissues. Analysis of the available literature indicates that soy protein can be fabricated into different shapes, being relatively easy to be processed by solvent or melt based techniques. Furthermore soy protein can be blended with other synthetic and natural polymers and with inorganic materials to improve the mechanical properties and the bioactive behavior for several demands. This review discusses succinctly the biomedical applications of SP based materials focusing on processing methods, properties and applications highlighting future avenues for research. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 104A: 553–569, 2016.